PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Waris, Nurjannah (Manajemen Bisnis, 2014)
This research aims to test the influence of corporate financial performance of banking corporate proxied on CAR, NPL, NIM, ROA, ROE, LDR, BOPO against stock prices on corporate banking in Indonesia stock exchange simultaneously and partial. The population in this study is banking company in Indonesia Stock Exchange amounted to 36 banks. Samples was determined by the method of purposive sampling in order to obtain 23 sample companies . The results of this research show that partially contributing significantly to the stock price is the NPL, ROA, and LDR. As for the CAR, ROE, NIM, BOPO had no significant effect on stock prices. Simultaneously shows there is influence between all independent variables on stock prices. The magnitude of the effect was 31,7% while the rest of 68,3% influenced other factors outside of research. The implications of this research shows that financial performance on certain conditions, have no effect on the decisions of investors in the capital markets.Keywords: Financial Performance, Stock Prices, Banking